2021
DOI: 10.1136/gutjnl-2020-323931
|View full text |Cite
|
Sign up to set email alerts
|

Alternative treatments for type 2 diabetes and associated metabolic diseases: medical therapy or endoscopic duodenal mucosal remodelling?

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“… 36,37 Several studies have confirmed GIP suppression following endoscopic DMR for MS treatment; however, adverse events are inevitable because of thermal energy. 17,38,39 Therefore, we focused on PDT-DMR to avoid affecting the deep mucosal layers. Na et al have confirmed the potential for treating obesity with T2DM by inhibiting GIP release from the K-cells using endoscopic PDT in an in vivo model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36,37 Several studies have confirmed GIP suppression following endoscopic DMR for MS treatment; however, adverse events are inevitable because of thermal energy. 17,38,39 Therefore, we focused on PDT-DMR to avoid affecting the deep mucosal layers. Na et al have confirmed the potential for treating obesity with T2DM by inhibiting GIP release from the K-cells using endoscopic PDT in an in vivo model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DMR methods using lasers, pulsed electric fields, radio frequency, steam, and cryoablation have been developed for other sites, such as the Barrett's esophagus; however, they are in pre-clinical trial stages and require procedural development for clinical application to humans. 17 …”
Section: Introductionmentioning
confidence: 99%
“…However, because of safety concerns, the DJBL does not seem to be an ideal treatment option for improving insulin resistance and other MetSyn parameters (71). Last, the DMR procedure ablates approximately 10-15 cm of the duodenal mucosa, to induce healthy regeneration thereof (72). It has been shown to significantly improve glycemic control, insulin resistance, and liver fat percentage in patients with T2D even in a controlled setting (73,74).…”
Section: Surgical and Endoscopic Interventionsmentioning
confidence: 99%
“…53 While the mechanisms may be multifactorial, an increase in GLP-1 levels and bile acids (at least in rodents) may be involved. Experimental, non-surgical procedures collectively called 'duodenal exclusion therapies'-which include the duodenal-jejunal bypass sleeve 54 and duodenal mucosal resurfacing 55 -have given related results regarding incretin secretion.…”
Section: Gastrointestinal Bypass Proceduresmentioning
confidence: 99%